Exploration of a novel object in late adolescence predicts novelty-seeking behavior in adulthood: Associations among behavioral responses in four novelty-seeking tests - Cuenya, Lucas (2016)
The sensation/novelty seeking behavioral trait refers to the exploration/preference for a novel environment. Novelty seeking increases during late adolescence and it has been associated with several neurobehavioral disorders. In this experiment, we asked whether inbred Roman high- and low-avoidance (RHA-I, RLA-I) rats (1) differ in novelty seeking in late adolescence and (2) whether late adolescent novelty seeking predicts this trait in adulthood. Thirty six male RHA-I and 36 RLA-I rats were exposed to a novel object exploration (NOE) test during late adolescence (pnd: 52-59; Dependent variables: contact latency, contact time, contact frequency). Head-dipping (hole-board, HB), time and visits to a novel-arm (Y-maze), and latency-in and emergence latency (emergence test) were registered in adulthood (pnd: 83-105). The results showed strain differences in all these tests (RHA-I > RLA-I). Factor analysis (RHA-I + RLA-I) revealed two clusters. The first one grouped HB and emergence test measures. The second one grouped NOE and Y-maze variables. Time exploring a novel object (NOE) was a significant predictor of novel arm time (RHA-I + RLA, RHA-I); contact latency was a significant predictor of novel arm frequency (RLA-I). Present results show consistent behavioral associations across four novelty-seeking tests and suggest that late adolescent novelty seeking predicts this genetically-influenced temperamental trait in adult Roman rats.